Wet steam measurement techniques - Walker, David; Barham, Scott; Giddings, Donald; Dimitrakis, Georgios (De Gruyter, 2018)
In recent years a greater need for power station efficiency has become evident; improving turbine blade efficiency is one of the methods proposed. This efficiency relies upon the wetness of the steam that comes into contact with the blades of the low pressure turbine stage in general and all turbines in nuclear power generation. Therefore being able to measure the moisture content of the steam in real time in conjunction with an accurate measure of steam velocity can give an overall mass flow re-entering the turbine, allowing for a feedback control. The system could rely on one technique that could measure suspended droplets and wall bound liquid film, or a combination of techniques could operate together. This work gives a comprehensive review of the different techniques used to measure the moisture content including the liquid film and moisture content and techniques that can give measurements on both simultaneously. Each technique has its strengths and weaknesses analysed, to see which technique works best overall and which techniques could be used together.